2004
DOI: 10.1038/sj.ijir.3901178
|View full text |Cite
|
Sign up to set email alerts
|

Serum androgen levels in healthy premenopausal women with and without sexual dysfunction: Part A. Serum androgen levels in women aged 20–49 years with no complaints of sexual dysfunction

Abstract: Androgen insufficiency is a recognized cause of sexual dysfunction in men and women. Age-related decrements in adrenal and gonadal androgen levels also occur naturally in both sexes. At present, it is unclear if a woman's low serum androgen level is a reflection of the expected normal age-related decline or indicative of an underlying androgen-deficient state. We studied premenopausal women with no complaints of sexual dysfunction to help define a normal female androgen profile. In all, 60 healthy, normally me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 24 publications
5
48
1
5
Order By: Relevance
“…Androgen signaling in female is very important for the differentiation of human endometrial stromal cells into decidual cell; a process is called decidualization that critically controls embryo implantation and placentation [11]. The effect of androgens such as testosterone and dihydrotestosterone mediated by androgen receptor (AR) that is a nuclear receptor [3].…”
Section: Introductionmentioning
confidence: 99%
“…Androgen signaling in female is very important for the differentiation of human endometrial stromal cells into decidual cell; a process is called decidualization that critically controls embryo implantation and placentation [11]. The effect of androgens such as testosterone and dihydrotestosterone mediated by androgen receptor (AR) that is a nuclear receptor [3].…”
Section: Introductionmentioning
confidence: 99%
“…There was no change in sex hormonebinding globulin. 41 Another study of 1423 women between 18 and 75 years old found similar decreases in premenopausal women, with no further decreases post-menopausally. 42 Several studies have evaluated androgen levels in women with HSDD, and these provide no definitive evidence of lower levels in HSDD compared to normal women.…”
Section: Androgens In Hypoactive Sexual Desire Disorder In Womenmentioning
confidence: 89%
“…La fisiología de la respuesta sexual viene extensamente descrita en los múltiples trabajos del Dr. Mas [38][39][40][41] . A continuación expondré un resumen orientado a ver qué aspectos de la fisiología de la RS pueden verse afectados por la histerectomía.…”
Section: Fisiología De La Respuesta Sexual Femeninaunclassified
“…Los ovarios y las glándulas suprarrenales comparten la producción de testosterona a partes iguales. Hay una disminución en la producción progresiva con la edad 38 . La insuficiencia de andrógenos es una causa reconocida de disfunción sexual.…”
Section: Fisiología De La Respuesta Sexual Femeninaunclassified
See 1 more Smart Citation